Theoretical prediction, preparation, and mechanical properties of YbB6, a candidate interphase material for future UHTCf/UHTC composites. Issue 15 (November 2016) - Zhou, Yanchun; Wang, Xiaofei; Xiang, Huimin; Feng, Zhihai; Wang, Guigen
Abstract: High melting point, low shear deformation resistance and high volume expansion upon oxidation are the basic requirements for interphase materials of future ultrahigh-temperature ceramic fiber reinforced ultrahigh-temperature ceramic matrix (UHTCf /UHTC) composites. YbB6 is one of the materials that possesses a combination of these properties. In this work, using a combination of first-principles calculations based on density functional theory and experimental investigations, low shear deformation resistance of YbB6 (theoretically predicted 81 GPa, experimentally determined 80 GPa) is confirmed. In addition, YbB6 has low Pugh's ratio G/B, low brittleness index M = Hv /KIC, but high damage tolerant index D t = K I C × E / σ b × H v, which endow that cracks are arrested or deflected when propagated from the matrix if it was used as an interphase material for UHTCf /UHTC composites. Details on the preparation, structural features and mechanical properties (hardness, strength, fracture toughness) of YbB6 are also given.